STRUCTURAL DYNAMICS OF BACTERIAL NITROREDUCTASE ENZYMES FROM A MINING-IMPACTED ENVIRONMENT IN SOUTH KALIMANTAN, INDONESIA: ARCHITECTURE FOR SUSTAINABLE CHROMIUM BIOREMEDIATION - Andifa Anugerah Putra; Munandar Ramadhani; Noer Komari; Badruzsaufari (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- New bacterial enzymes found in Indonesian soil can neutralize toxic chromium waste.- These unique bacteria show great promise for bioremediation in polluted mining soils.- One of the newly found enzymes from these bacteria has a superior, highly stable structure.- This superior stability is key, coming from a rigid core with flexible moving loops.- This research provides a molecular blueprint for engineering enzymes to clean up chromium.ABSTRACTHexavalent chromium [Cr(VI)], a soluble and carcinogenic industrial pollutant, poses a significant threat to both the environment and human health, necessitating effective remediation strategies. Microbial enzymatic reduction of Cr(VI) to its less toxic trivalent state, Cr(III), is a promising approach. However, growing evidence suggests that many enzymes involved in this process are flavin mononucleotide (FMN)-dependent reductases, which likely reduce Cr(VI) adventitiously via a reduced flavin intermediate, rather than through direct enzymatic catalysis. This study presents a comparative computational analysis of two novel FMN-dependent reductases, designated M2Cr10 and M54Cr10, derived from chromium-tolerant bacteria Acinetobacter radioresistens and Bacillus tropicus, respectively, which were isolated from Indonesian serpentine soil. Phylogenetic and sequence analyses classified both enzymes as members of the FMN-dependent nitroreductase superfamily. High-quality homology models were generated and validated, with over 95% of residues occupying the most favored regions of the Ramachandran plot, confirming their stereochemical integrity. Molecular docking simulations predicted strong binding affinities for the FMN cofactor, with binding energies of -7.1 kcal/mol for M2Cr10 and -8.1 kcal/mol for M54Cr10. These interactions are stabilized by a network of hydrogen bonds and hydrophobic contacts, with residue Tyr¹³¹ identified as a key anchor for the FMN isoalloxazine ring in both enzymes. Extensive 10-nanosecond molecular dynamics simulations revealed that the A. radioresistens M2Cr10 enzyme exhibits superior structural architecture characterized by greater global stability, as indicated by lower average root mean square deviation (RMSD) and solvent-accessible surface area (SASA). However, it also displays greater localized flexibility (higher RMSF) in functional loop regions critical for catalysis. This combination of a rigid scaffold and dynamic functional loops suggests that M2Cr10 may be a more robust and potentially efficient biocatalyst. These findings provide a detailed molecular blueprint for understanding the structural determinants of stability in FMN-dependent reductases and offer a rational basis for engineering these enzymes for more effective adventitious bioremediation of Cr(VI).